2013
DOI: 10.1111/jvp.12084
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of buprenorphine following intravenous and buccal administration in cats, and effects on thermal threshold

Abstract: This study reports the pharmacokinetics of buprenorphine, following i.v. and buccal administration, and the relationship between buprenorphine concentration and its effect on thermal threshold. Buprenorphine (20 μg/kg) was administered intravenously or buccally to six cats. Thermal threshold was determined, and arterial blood sampled prior to, and at various times up to 24 h following drug administration. Plasma buprenorphine concentration was determined using liquid chromatography/mass spectrometry. Compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 38 publications
(76 reference statements)
3
41
3
Order By: Relevance
“…The pharmacokinetic parameters estimated in the current study are similar to those reported in the literature (Table 3) using buprenorphine in cats [9, 16, 18, 25]. Some variability exists due to different bioavailability particularly in routes other than IV.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The pharmacokinetic parameters estimated in the current study are similar to those reported in the literature (Table 3) using buprenorphine in cats [9, 16, 18, 25]. Some variability exists due to different bioavailability particularly in routes other than IV.…”
Section: Discussionsupporting
confidence: 82%
“…Traditional methods used for pharmacokinetic modeling of buprenorphine in cats have studied each route of administration separately [9, 16, 18], instead of pooling data from crossover studies to strengthen estimation of parameters shared across routes of administration (CL, V1, CL2, V2). In the present study, six individuals were used in a typical cross-over design, yielding 18 related (six cats, three routes of administration) plasma concentration-time curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…administration of buprenorphine. In agreement with our results, a comparable low bioavailability of buprenorphine following OTM administration was observed in a previous study in cats that also used LC‐MS/MS to analyse buprenorphine (Hedges et al ., ).…”
Section: Pharmacokinetic Parameters Of Dexmedetomidine After Otm (Oramentioning
confidence: 97%
“…), although more recent studies have found inconsistent effects and lower bioavailability than previously reported (Hedges et al. , b; Steagall et al. , ).…”
Section: Introductionmentioning
confidence: 87%